Natural biomolecules in leaves and fruit extracts mediate the biosynthesis of SnO₂ nanoparticles: a mini review / Irmaizatussyehdany Buniyamin ... [et al.] - Buniyamin, Irmaizatussyehdany; Abd Halim, Muhamad Faizal; Eswar, Kevin Alvin; J. Jalani, Kathleen; Syed Abd Kadir, Syed Abdul Illah Alyahya; Mohammad, Maryam; Idorus, Mohd Yusri; Asli, Noor Asnida; Mahmood, Mohamad Rusop; Khusaimi, Zuraida (Faculty of Pharmacy, 2023)
The green approach of nanoparticle preparation via biosynthesis method is known to be more economical, less toxic, and environmental-friendly as compared to the conventional chemical and physical methods which are hazardous and expensive. The advantages that are offered by this nanoscale material are their high surface area to volume ratio and the great stability which drive the performance to be effective. Among several nanoparticles, metal oxide namely tin (iv) oxide nanoparticles (SnO 2 NPs) have attracted significant attention in recent years specifically in the nanotechnology discipline due to its wide applications in medical, catalysis, energy storage, coatings, sensors, dye-sensitized solar cells, and optoelectronics. The biosynthesis method was reported to be conducted using an aqueous extract of the green part of the plant, mostly the leaves and fruit segment. Within these plant parts, rich amounts of natural biomolecules are available that are capable of mediating the synthesis mechanism through capping and reducing action, which involves the chelating activity. Several characterization techniques were carried out to determine their unique characteristics in terms of crystallinity and morphological aspects such as XRD, TEM, SEM, EDX, FTIR, and UV-Vis. This paper summarizes the biosynthesis works of SnO2 NPs using leaves and fruit extract, and their properties were tested based on the photocatalytic performance as well as biomedical activities such as antimicrobial, antibacterial, antioxidant, and cytotoxicity.